Effect of groundnut cake and P on millet stover utilisation and nutrient excretion by sheep - Sangare, M.; Fernández Rivera, S.; Hiernaux, Pierre H.Y.; Pandey, V.S. (2002)
An experiment, was conducted in semi arid Niger to determine the influence of supplementation with groundnut cake (GC) )0 g kg 1, 2.5 g kg 1, 5 g kg 1, and 7.5 g kg 1 live weight (LW)) and P (0 g day`' and 3 g day 1 animal 1) on diet and millet stover intake and digestibility, sheep growth rate, and nutrient excretion. Total digestible organic matter intake (DOMI, g kg 1 LW° 75) increased 4.24 ± 1.26 g g'1 of GC and decreased 0.31 ± 0.16 g g 1 GCz, and increased (P #.0.10) with P.. supplementation. Millet stover intake (g kg 1 LM was related to GC level by both linear (1.79 ± 0.53 g g 1 GC) and quadratic ( 0.20 ± 07 ~ g'1 GCZ functions and to P supplementation by linear function (0.87 ± 0.46 g g 1 P). No effect of GC X P interaction was observed. 1t equal level of GC, P supplementation increased stover intake by 2 20%. Diet digestibility increased linearly (P < 0.01) with GC level, but no effect of P supplementation was observed. Digestibility of neutral detergent fibre was unaffected by either GC or P level. Animals supplemented with P had adequate P (0.2496) in their diet in contrast with those unsupplemented 0.05 0.1896). Live weight gain (g y') increased 22.10 ± 3.10 g g 1 GC and decreased 1.5 ± 0.39 g GCz. Live weight gain response to P supplementation (7.33 ± 1.66 g g'' of P) was independent of GC level. Nitrogen concentration in faeces )g Itg'1 faeces dry matter (DM)) Increased linearly both by GC and P supplementation, whereas urinary N (g L 1) was only influenced by GC level. Faecal P (g kg 1 FDM) increased about three fold with P supplementation. It is concluded that an adequate capture of the additional N and P that is voided following supplementation, could enhance the sustainability of mixed farming systems in the Sahel.